Analisis Yuridis Perlindungan Privasi Terhadap Pengambilan Foto Tanpa Izin Di Era Digital - Muhammad Isya, Ibrahim; Wardani, Susilo (JURNAL PENELITIAN SERAMBI HUKUM, 2025)
The development of digital technology has significantly influenced various aspects of human life, including the emergence of critical issues related to violations of personal privacy rights. One widespread form of violation is the unauthorized taking and dissemination of photographs on social media. This phenomenon endangers individual rights and may also breach legal standards, particularly concerning personal data protection. This study aims to evaluate legal protection against the unauthorized taking and dissemination of photographs based on Law Number 27 of 2022 concerning Personal Data Protection (PDP Law), as well as to identify the challenges and legal efforts in its enforcement. The research method used is normative legal research, applying statutory and conceptual approaches, with data collection carried out through a literature review of primary and secondary legal documents. The findings indicate, first, that legal protection against the unauthorized taking and dissemination of photographs in the digital era as regulated under the PDP Law includes both normative and procedural protections, along with the imposition of legal sanctions on violators. Every activity of collecting, storing, processing, and disseminating photographs must be based on the explicit consent of the data subject. Second, the implementation of the PDP Law still faces serious challenges, such as the absence of an independent supervisory authority, low public literacy regarding privacy, weak legal proof capacity by law enforcement, and the lack of standardized guidelines for explicit consent